Vitamin E, Turmeric and Saffron in Treatment of Alzheimer's Disease - Nur Adalier; Heath Parker (MDPI AG, 2016)
Alzheimer's disease (AD) is a growing epidemic and currently there is no cure for the disease. The disease has a detrimental effect on families and will strain the economy and health care systems of countries worldwide. The paper provides a literature review on a few ongoing possible antioxidant therapy treatments for the disease. The paper highlights use of vitamin E, turmeric and saffron for an alternative antioxidant therapy approach. Clinical studies report their therapeutic abilities as protective agents for nerve cells against free radical damage, moderating acetylcholinesterase (AChE) activity and reducing neurodegeneration, which are found as key factors in Alzheimer's. The paper suggests that future research, with more clinical trials focused on more natural approaches and their benefits for AD treatment could be worthwhile.